2014
DOI: 10.1097/aog.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Lifestyle Intervention for Women With Recent Gestational Diabetes Mellitus

Abstract: Objective To test the feasibility and effectiveness of a web-based lifestyle intervention based on the Diabetes Prevention Program modified for women with recent gestational diabetes mellitus (GDM) to reduce postpartum weight retention. Methods We randomly allocated 75 women with recent GDM to either a web-based lifestyle program (Balance after Baby) delivered over the first postpartum year or to a control group. Primary outcomes were change in body weight at 12 months from 1) first postpartum measured weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(176 citation statements)
references
References 27 publications
3
172
1
Order By: Relevance
“…13 Recent interventions focused on preventing later-life diabetes among women with gestational diabetes have proven successful at reducing diabetes risk factors such as post-partum weight retention through relatively simple lifestyle interventions delivered via web and mail/telephone. 14,15 Such work provides a possible template for similar low-cost interventions aimed at improving short term and long term cardiovascular health among women with placental syndromes.…”
mentioning
confidence: 99%
“…13 Recent interventions focused on preventing later-life diabetes among women with gestational diabetes have proven successful at reducing diabetes risk factors such as post-partum weight retention through relatively simple lifestyle interventions delivered via web and mail/telephone. 14,15 Such work provides a possible template for similar low-cost interventions aimed at improving short term and long term cardiovascular health among women with placental syndromes.…”
mentioning
confidence: 99%
“…The range of mean age participant age was 32.2 to 62 years. The studies enrolled between 47-93% females, with the exception of two studies recruiting specifically women with a history of gestational diabetes (Ferrara et al, 2011;Nicklas et al, 2014) and two studies enrolling predominantly men (95% and 97%) (DeJoy et al, 2013;Wilson et al, 2015). Racial and ethnic diversity of participants varied from studies of only minority populations (African American, Hispanic/Latino, Asian/Pacific Islander) to studies of 19-100% White, non-Hispanic participants.…”
Section: Study Design and Participant Characteristicsmentioning
confidence: 97%
“…Session content related to physical activity varied, but included the key principles of the DPP such as ways to safely increase PA, addressing barriers to PA, and changing environmental and social cues relating to PA. Thirteen studies included PA sessions or supervised exercise as an option for participants (Amundson et al, 2009;Guyse et al, 2011;Harwell et al, 2011;Islam et al, 2013;Jaber et al, 2011;Ma et al, 2013;Matvienko and Hoehns, 2009;McBride et al, 2008;Vadheim et al, 2010a;Vadheim et al, 2010b;Endevelt et al, 2015;Kutob et al, 2014;Swanson et al, 2012), three studies offered free fitness center membership (Aldana et al, 2005;Seidel et al, 2008;Nicklas et al, 2014), and two studies offered participants access to onsite resources for PA (Ackermann et al, 2008;Barham et al, 2011).…”
Section: Lifestyle Intervention: Physical Activity Goals and Contentmentioning
confidence: 98%
“…Women in the control group received usual care from their healthcare providers. 56 The pilot results showed that women in the intervention group lost a mean of 2.8 kg from 6 weeks to 12 months postpartum compared to the control group who gained a mean of 0.5 kg. The study is currently being scaled up to include more sites, English and Spanish language versions, and 2 years of follow-up to examine maintenance of weight loss after the intervention is complete.…”
Section: Introductionmentioning
confidence: 97%